Representasi Matematika di Media Sosial sebagai Prediktor Persepsi Publik terhadap Matematika: Analisis Regresi Logistik Ordinal - Zakiyatur Rosidah; Sri Harini (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2026)
Public perception of mathematics is often characterized by negative views, despite its fundamental role in everyday life and human development. This study aims to examine the effects of mathematics anxiety, teacher instructional quality, mathematics learning experience, and the representation of mathematics on social media on public perceptions of mathematics. A quantitative approach with an explanatory survey design was employed. Data were collected through an online questionnaire using a five-point Likert scale from 100 respondents from the general public who had previously participated in formal mathematics education. Ordinal logistic regression was used for data analysis. The results indicate that the regression model is statistically adequate and demonstrates good model fit. Mathematics anxiety, teacher instructional quality, and mathematics learning experience do not have a significant effect on public perceptions of mathematics. In contrast, the representation of mathematics on social media has a positive and significant influence on public perception. These findings suggest that contemporary experiences through social media play a more prominent role in shaping public perceptions of mathematics than past formal learning experiences. This study contributes theoretically to the literature on mathematics perception in public contexts and provides practical implications for developing effective strategies to promote positive representations of mathematics in digital spaces.